IMPLEMENTASI METODE WORDWALL BERBASIS LITERASI DIFERENSIASI UNTUK MENINGKATKAN MINAT BACA SISWA KELAS 2 DI SDN DANGDANG 1 - Yusri; Encep Supriatna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the implementation of Wordwall method based on differentiation literacy to improve reading interest in elementary school students. The study employed a mixed-methods approach with a quasi-experimental design. Research subjects involved 60 students grade 2 from SDN DANGDANG 1. Research instruments included literacy tests, reading interest questionnaires, observations, and in-depth interviews. Sampling technique used purposive sampling with experimental and control group divisions. Research results demonstrated a significant increase in students' reading interest, with an average literacy score improvement of 67.3% in the experimental group. Statistical analysis using independent t-test showed significant differences between experimental and control groups. The Wordwall method based on differentiation literacy proved effective in improving reading motivation and abilities of elementary school students.